A novel pancreatic cancer model originated from transformation of acinar cells in adult tree shrew, a primate-like animal - Qiu Tu; Dong Yang; Xianning Zhang; Xintong Jia; Sanqi An; Lanzhen Yan; Hongjuan Dai; Yuhua Ma; Chengwei Tang; Weimin Tong; Zongliu Hou; Longbao Lv; et al. (The Company of Biologists, 2019)
Pancreatic cancer is one of the most lethal common cancers. The cell of origin of pancreatic ductal adenocarcinoma (PDAC) has been controversial, and recent evidence suggested acinar cells as the most probable candidate. However, the genetic alterations driving the transformation of pancreatic acinar cells in fully mature animals remain to be deciphered. In this study, lentivirus was used as a tool to introduce genetic engineering in tree shrew pancreatic acinar cells to explore the driver mutation essential for malignant transformation, establishing a novel tree shrew PDAC model, because we found that lentivirus could selectively infect acinar cells in tree shrew pancreas. Combination of oncogenic KRASG12D expression and inactivation of tumor suppressor genes Tp53, Cdkn2a and Cdkn2b could induce pancreatic cancer with full penetrance. Silencing of Cdkn2b is indispensable for Rb1 phosphorylation and tumor induction. Tree shrew PDAC possesses the main histological and molecular features of human PDAC. The gene expression profile of tree shrew PDAC was more similar to human disease than a mouse model. In conclusion, we established a novel pancreatic cancer model in tree shrew and identified driver mutations indispensable for PDAC induction from acinar cells in mature adults, demonstrating the essential roles of Cdkn2b in the induction of PDAC originating from adult acinar cells. Tree shrew could thus provide a better choice than mouse for a PDAC model derived from acinar cells in fully mature animals.